A new high resolution optical method for obtaining the topography of fracture surfaces in rocks - Ogilvie, Steven (Image analysis and stereology, 2002)
Surface roughness plays a major role in the movement of fluids through fracture systems. Fracture surface profiling is necessary to tune the properties of numerical fractures required in fluid flow modelling to those ofreal rock fractures. This is achieved using a variety of (i) mechanical and (ii) optical techniques. Stylus profilometry is a popularly used mechanical method and can measure surface heights with high precision, but only gives a good horizontal resolution in one direction on the fracture plane. This methodis also expensive and simultaneous coverage of the surface is not possible. Here, we describe the development of an optical method which images cast copies of rough rock fractures using in-house developed hardware and image analysis software (OptiProfrM) that incorporates image improvement and noise suppression features. This technique images at high resolutions, 15-200 micro m for imaged areas of 10 x 7.5 mm and 100 x 133 mm, respectively and a similar vertical resolution (15 pm) for a maximum topography of 4 mm. It uses in-house developed hardware and image analysis (OptiProfrM) software and is cheap and non-destructive, providing continuous coverage of the fracture surface. The fracture models are covered with dye and fluid thicknesses above the rough surfaces converted into topographies using the Lambert-Beer Law. Thedye is calibrated using 2 devices with accurately known thickness; (i) a potycarbonate tile with wells of different depths and (ii) a wedge-shaped vialmade from silica glass. The data from each of the two surfaces can be combined to provide an aperture map of the fracture for the scenario where thesurfaces touch at a single point or any greater mean aperture. The topography and aperture maps are used to provide data for the generation of synthetic fractures, tuned to the original fracture and used in numerical flowmodelling.
Keywords: površine; preiskava materiala; hrapavost; optične metode